Skills, Tasks, and Complexity - Hans Gersbach; Samuel Schmassmann (Institute of Labor Economics (IZA), 2019)
We introduce a new task-based framework to describe production. It focuses on the fact that certain tasks are too complex for many workers to perform. In such an environment, the relationship between wages of workers may significantly differ from their relative productivities. The labor market partitions itself into submarkets, in which wages and productivity are aligned, and high-skilled workers may obtain wage premia above their productivity level. The framework offers a variety of applications. For instance, the automation of low-complexity tasks tends to reinforce labor market segmentation. Moreover, comparatively small changes in a task's complexity, via new products, processes or automation, may have either a negligible or a large impact on wage inequality.
Keywords: O31; O38; 330; skill; technological change; tasks; complexity